Influence of Intelligent Assitive Technology on the Daily Activities of Visually Impiared People - Nombakuse, Ronaldo (Department of Information Systems, 2024)
Background: South Africa has 1.4 million visually impaired people (VIPs) due to various causes of vision impairment. Vision impairment significantly impacts VIP functional capabilities, leading to affected individuals living less than optimal lives. Intelligent assistive technologies (IATs) provide essential support for VIPs' daily living activities (ADLs). These IATs include communication, mobility, visual, and daily activity assistive devices. Studies conducted within the Information Systems (IS) field focused on the adoption, usage, accessibility, usability, and acceptability of IATs among VIPs. However, more research is needed to explain the influence of IATs on the daily activities of visually impaired people post-adoption. Aims: The main objective of this study was to explain the influence of intelligent assistive technologies on the activities of daily living of visually impaired people. Secondarily, the study aimed to identify the factors affecting access to IATs by VIPs, and the benefits and drawbacks of intelligent assistive technologies on the ADLs of VIPs. Methods: This study employed subjectivism as an ontology and interpretivism as an epistemology. A crosssectional qualitative case study strategy was adopted. Semi-structured interviews (N=25) and an online qualitative survey (N=37) were the primary data sources, while a document review was used as a secondary data source. NVivo 12 was used for qualitative data analysis. Qualtrics was used for the online qualitative survey while AudioMass was used for voice editing of interviews. Only visually impaired people who had access to IATs and were above eighteen years old were purposefully sampled. Data was analysed both deductively and inductively. Data was tested deductively using the operationalised Capability Approach constructs. An inductive cycle of data analysis was also conducted. All the university's ethical considerations were observed since this study involved vulnerable people. Key Findings: The study found that intelligent assistive technologies have the potential to improve the lives of visually impaired people to: a) live the lives they wish to live, b) enhance capabilities to perform their activities of daily living, c) gain financial and economic freedom. However, due to low employment opportunities among VIPs, affordability emerged as a significant restriction for access to suitable IATs. Additionally, the development outcomes that visually impaired people achieve when they use IATs include the following: a) enhanced employability; b) better access to information and enhanced intellectual stimulation; c) improved communication skills; d) ability to perform and participate in spiritual activities; d) the ability to manage health outcomes; and improved mobility. Contribution of Study: The study contributes to knowledge by empirically demonstrating the complex relationships between accessibility and the use of IATs by VIPs using semi-structured interviews and a qualitative survey. Secondly, the research proposes seven propositions that future researchers can utilise to develop the lives of visually impaired people. Finally, the study also provides policymakers insights into policy gaps related to the affordability, accessibility, and usability challenges of IATs by visually impaired people.